Quality of human capital and economic growth - Mansyur, Khusnul Khotimah (Professorline, 2024)
The quality of human capital is a separate capital that can be compared to physical capital when creating production in the country. Therefore, improving the quality of human capital is very strategic in terms of economic growth, and the article also claims that there are two critical points in the correlation between human capital and economic growth. First, human capital must be given the same priority as other factors of economic growth. Second, human capital has a significant impact economic growth. Poor quality of human capital can negatively affect economic growth. It is known that the quality of human capital is a type of capital that can be identified with physical capital/natural resources when creating production in a country. Therefore, improving the quality of human capital is very strategic from the point of view of economic growth. At this point, we recognize two essential points in the correlation between human capital and economic growth. First, human capital must be given the same priority as other factors of economic growth. Second, human capital has a significant impact economic growth.